EXPERIMENTAL ESTIMATE OF THE HEATING APPLIANCES HEAT FLOW PARAMETERS - Pukhkal, Viktor (Journal of Applied Engineering Science, 2014)
The knowledge of radiant and convective heat flows distribution from heating appliances is required for a development of an efficient heating systems maintaining necessaryconditions in rooms at the lowest energy requirements. The study method is developed and provided. The heating appliances of water heating system (convection heater and radiator) are studied. The results of heating appliances heat flow measurements are given. Radiant and convective components of heating appliances heat flow are determined.